Postcolonial Citizens and Ethnic Migration - O. Sharpe, Michael. author. aut Link
XIII, 283 p.
Keywords: This book provides a cross-regional investigation of the role of citizenship and ethnicity in migration, political incorporation, and political transnationalism in the age of globalization, exploring the political realities of Dutch Antilleans in the Netherlands and Latin American Nikkeijin in Japan.